Systems, Software and Service Process Improvement 18th European Conference, EuroSPI 2011, Roskilde, Denmark, June 27-29, 2011. Proceedings - e; Pries-Heje, Jan.; Messnarz, Richard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume constitutes the refereed proceedings of the 18th EuroSPI conference, held in Roskilde, Denmark, in June 2011. The 18 revised full papers presented together with 9 key notes were carefully reviewed and selected. They are organized in topical sections on SPI and assessments; SPI and implentation; SPI and improvement methods; SPI organization; SPI people/ teams; SPI and reuse; selected key notes for SPI implementation.
Keywords: Computer science; Software engineering; Information systems; Information Systems; Computer Science; Software Engineering; Information Systems Applications (incl.Internet).; Programming Languages, Compilers, Interpreters; Management of Computing and Information Systems; Programming Techniques; Software Engineering/Programming and Operating Systems